Alterations of Suckling Piglet Jejunal Microbiota Due to Infection With Porcine Epidemic Diarrhea Virus and Protection Against Infection by Lactobacillus salivarius - Dong, Wanting; Ding, Ning; Zhang, Yu; Tan, Zhen; Ding, Xiangdong; Zhang, Qin; Jiang, Li (Frontiers in Veterinary Science, 2021)
The high mortality of neonatal piglets due to porcine epidemic diarrhea virus (PEDV) infection has caused huge economic losses to the pig industry. The intestinal microbiota is an important barrier against invaders entering the gastrointestinal route. In this study, we examined the differences between intestinal microbiota of PEDV-infected and healthy piglets. According to the viral copy numbers, 16 crossbred (Landrace-Yorkshire) piglets were divided into three groups: uninfected, low virus load, and high virus load groups. Next, 16S rRNA sequencing was performed to determine the microbiota composition in jejunal content and jejunal mucosal samples from the three groups. PEDV infection induced an imbalance in the microbiota of both jejunal content and jejunal mucosa. The abundance of phylum Firmicutes was higher in uninfected piglets than in infected piglets, whereas the abundance of Proteobacteria was lower in uninfected piglets. Principal coordinate analysis showed significant separation of jejunal microbiota between different groups. Linear discriminant analysis (LDA) effect size (LEfSe) identified Lactobacillus salivarius as a potential biomarker among three groups at the level of species. Then, in vitro, L. salivarius was able to suppress the infection of PEDV to IPEC-J2 cells and decreased the expression of GRP78 (Glucose-regulating protein 78). In addition, we detected the mRNA expression of genes involved in the FAK/PI3K/Akt signaling pathway. When IPEC-J2 cells were treated with L. salivarius before PEDV infection, the mRNA expression levels of ITGA1, ITGA5, ITGB5, FAK, PIK3R1, PIK3CA, and AKT1 were significantly higher than those in the control cells (without treatment) at different times post-infection, indicating that L. salivarius may upregulate the FAK/PI3K/Akt signaling pathway in IPEC-J2 cells to resist PEDV infection. In summary, PEDV infection altered microbial communities in both jejunal content and jejunal mucosa. L. salivarius has a protective effect against PEDV infection in IPEC-J2 cells. This study provides a potentially effective strategy to prevent the occurrence and control the spread of PED in the pig production.